Comparison of oral iron and injectable iron for the prevention of iron deficiency anemia in baby pigs - K B Beeman; D A Schoneweis (Kansas Agricultural Experiment Station Research Reports, 1992)
One of two oral iron compounds or an injectable iron (100 mg iron per treatment) were administered to pigs on d 1 and 15 postfarrowing, and they were compared with untreated littermates. There was no significant difference between the pigs receiving the oral iron and the negative controls in serum iron or total iron binding capacity. Pigs that received iron by injection had higher serum iron and packed cell volume and a lower total iron binding capacity compared with pigs given oral iron or untreated controls.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Piglet; Iron; Anemia